Exploring Students’ Motivation in Learning English at English Laboratory of UBL - Eka Sari Ayu; Yanuar Dwi Prastyo (English Language Education and Current Trends (ELECT), 2023)
Motivation is essential when learning a language, even English. Without motivation, a person will lack the will or excitement to learn, which can jeopardize his academic achievement. The purpose of this study is to measure the amount of motivation of students in learning English and the prevailing motivation, whether intrinsic or extrinsic motivation. The study was carried out at the University of Bandar Lampung's language laboratory in the 2022/2023 academic year. The descriptive qualitative method was utilized by the researchers in this study. A questionnaire was utilized as the research tool, and interviews were conducted. 192 third semester students from the University of Bandar Lampung's language laboratory took part in this study. The findings of this study are that the average student has a high level of motivation based on the interpretation of the total score (4.26). The dominant student motivation in learning English is intrinsic motivation, with a total score of 4.26. In contrast, extrinsic motivation is a score of 3.94, which is defined as a moderate level of motivation. It can be concluded that students who study at the language laboratory at the University of Bandar Lampung have high motivation in learning English and are more dominant in having intrinsic motivation which means they learn English because of a desire from within themselves.   REFERENCES Alizadeh, M. (2016). The impact of motivation on English language learning. International Journal of Research in English Education, 1(1), 11-15. Anjomshoa, L., & Sadighi, F. (2015). The importance of motivation in second language acquisition. International Journal on Studies in English Language and Literature (IJSEL), 3(2), 126-137. Arikunto,S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik. Buku.Rineka Cipta. Jakarta. 431 hlm. Aydogan, H. (2016). Intrinsic and extrinsic motivation for English learning scale (IEM-ELS): A psycholinguistics study of reliability and validity. MCBU Sosyal Bilimber Dergisi, 14(3), 55-65. Doi: 10.18026/cursos.66920 Bogdan dan Taylor, 1975 dalam J. Moleong, Lexy. (1989). Metodologi Penelitian Kualitatif. Bandung: Remadja Karya. Brown, H. (2007). Principles of Language Learning and Teaching. 5 th edition. Addison Wesley Longman, Inc. A Pearson Education Company. Dahliana, S. (2019). Students’ motivation and responsive pedagogy in language classroom. Englisia, 6(2), 75-87. Doi 10.22373/ej. v6i2.4601 Destrini, H., Nirwana., & Sakti. I. (2018). Penerapan model pembelajaran penemuan terbimbing (Guided discovery learning) untuk meningkatkan hasil belajar dan keterampilan proses sains siswa. Jurnal Kumparan Fisika. 1(1), 13-21. Doi: 10.33369/jkf.1.1.13-21 Elliot, Andrew J; Covington, Martin, (2001) “Approach and Avoidance Motivation", Educational Psychology Review. Fachraini, S. (2017). An analysis of students’ motivation in studying English (A survey study at UIN Ar-Raniry Banda Aceh). Getsempena English Education Journal, 4(1), 47-57. Fadilah, F. (2015). Teaching speaking skills using problem solving activities (experimental research in Speaking 1 at the first semester of IAIN Salatiga in the academic year of 2014/2015). (Unpublished thesis). Salatiga: IAIN Salatiga. Fachraini, S. (2017). An Analysis of Students Motivation in Studying English. Getsempena English Education Journal, 4(1), 47-57. Gardner, R. C. (2004). Attitude/motivation test battery: International AMTB research project (English version), 1-12. Gharib, S. (2019). Students’ motivation towards learning English: The case of a private university in Slemani. (Unpublished thesis). Nicosia: Near East University. Hayikaleng, N., Nair, S. M., & Krishnasamy, H. N. (2016). The Students Motivation on English Reading Comprehension. Utara Malaysia University: Malaysia. Harmer, J. (2007). The Practice of English Language Teaching. Fourth Edition. Malaysia Pearson Education Limited Jalinus, N., Nabawi, R. A., & Mardin, A. (2017). The seven steps of project-based learning model to enhance productive competences of vocational students. Advance in Social Science, Educational and Humanities Research, 102, 251256. Doi: 10.2991/ictvt-17.2017.43 Mahadi, T. S. T., & Jafari, S. M. (2012). Motivation, its types, and its impacts in language learning. International Journal of Business and Social Science, 3(24), 230-235. McMillan, James H., and Jessica Hearn. "Student self-assessment: The key to stronger student motivation and higher achievement." Educational horizons. 87.1 (2008): 40-49. Pratiwi, F. D. (2015). The learning motivation and preferred learning activities of successful students of English education study program at Universitas Bengkulu. (Unpublished Thesis). Bengkulu: University of Bengkulu Rahman, H. A., Rajab, A., Wahab, S. R. H., Nor, F. M., Zakaria, W. Z.W., & Badli, M. A. (2017). Factor affecting motivation in language learning. International Journal of Information and Education Technology, 7(7), 543-Doi:10.18178/ijiet.2017.7.7.927 Rafasah, N. (2019). The correlation between students’ motivation and their achievement in studying English. A correlational study at SMAN 1 Woyla. (Unpublished thesis). Banda Aceh: UIN Ar-Raniry University. Ratnasari., & Mela, D. (2011). Students’ learning style preferences (A study on fourth semester of the English department Muhammadiyah of Purwokerto in the academic year 2011/2012). (Unpublished thesis). Purwokerto: Muhammadiyah University. Risfayanti, L., Sofian, H., & Husin, F. (2015). An analysis of external factors influencing students' English learning achievements. Journal Pendidikan dan Pembelajaran Khatulistiwa, 4(5), 1-7. Roopa, s., & Satya, R. M. (2012). Questionnaire designing for a survey. The Journal of Indian Orthodontic Society, 46(4), 273-277. Doi: 10.5005/jp- journals 10021-1104 Santrock, W. John (2004) Educational Psychology. 2 nd Ed. New York: Hill Samejon, K. (2015). Extrinsic motivation factors in learning English as a second language. Kaalam, 1(1), 35-53. Sugeng, B., & Suryani. A. W. (2018). Presentation-based learning and peer evaluation to enhance active learning and self-confidence in the financial management classroom. Malaysian Journal of Learning and Instruction, 15(1), 173-201 Tambunan, A. R., & Siregar, T. (2016). Students’ motivation in learning English language (a case study electrical engineering department students). The Journal of Language Studies, 1(02), 63-70. Thohir, L. (2017). Motivation in a foreign language teaching and learning. Vision: Journal for Language and Foreign Language Learning, 6(1), 20-28. Doi: 10.21580/vjv6i11580. Wagiyo, S. (2018). Analysis of students’ motivation in learning English at senior high schools. Wasserman, J., Davis. C., & Astrab, D. P, (2009). Activity Design Handbook. 906 Lacey Ave, Suite 206: Pacific crest. Murp, J. (2011). How You and Your Mate Can Become a Super Couple. USA: Xlibr